I Am an African American: Distinguishing Between African American and African Applicants in Medical School Admissions Matters. (September 2018) - Baugh, Reginald F.
Abstract : Ignoring the diverse and rich cultures and histories of Africa and the African diaspora by applying the term African American to anyone of sub-Saharan African ancestry in medical school admissions does a disservice to applicants, medical schools, and the communities they serve. To determine how applicants can contribute to a diverse educational environment, admissions decisions must go beyond racial and ethnic self-reporting and recognize the diversity that applicants bring to their medical school. Using a holistic approach, institutions can fairly evaluate applicants and strategically fill their incoming classes. What each medical school is looking for based on its mission and how each student reflects that mission and enhances the educational environment should be revisited as each application is considered. Medical schools must adopt practices that strategically enroll applicants who help achieve their mission and better the communities they serve. The benefits of diversity are not achieved in a linear fashion but require a critical mass for each diverse group. Different strategies are needed to enhance the educational environment, address underrepresentation in medicine, and eliminate health disparities. If racial justice and health equity are to be realized, diversity policies need to recognize the differences between African and Afro Caribbean immigrants and African Americans. In this Perspective, the author argues for distinguishing between these groups in medical school admissions. He explores the differences in their history, culture, and experiences and demonstrates their uniqueness. He concludes by discussing diversity in medicine and offering suggestions for considering diversity in medical school admissions.